Giant Pulsations Excited by a Steep Earthward Gradient of Proton Phase Space Density: Arase Observation. Issue 14 (20th July 2018) - Yamamoto, Kazuhiro; Nosé, Masahito; Kasahara, Satoshi; Yokota, Shoichiro; Keika, Kunihiro; Matsuoka, Ayako; Teramoto, Mariko; Takahashi, Kazue; Oimatsu, Satoshi; Nomura, Reiko; Vellante, Massimo; Heilig, Balázs; et al.
Abstract: We present observational evidence of drift resonance between westward propagating odd mode standing ultralow frequency waves and energetic protons. Compressional ∼13 mHz (Pc4 band) waves and proton flux oscillations at >50 keV were detected at ∼03 hr magnetic local time by the Arase satellite on 15 April 2017. The azimuthal wave number ( m number) is estimated to be ∼−50 from ground observations, while the theory of drift resonance gives m ∼− 49 for odd mode waves and ∼110‐keV protons, providing evidence that the drift resonance indeed took place in this event. We also found a steep earthward gradient of proton phase space density, which can quantitatively explain the wave excitation. The observed waves show typical features of giant pulsations (Pgs), regarding local time, m number, and flux oscillations. This study, therefore, has great implications to the field line mode structure and excitation mechanism of Pgs. Plain Language Summary: The Arase satellite of Japan Aerospace Exploration Agency was launched on 20 December 2016 into an elliptical orbit with the apogee of 6  R e . On 15 April 2017, Arase was able to observe a giant pulsation (Pg) that is a kind of ultralow frequency waves with a large amplitude on the ground. The excitation mechanism of Pg has been studied by many authors but is not determined yet. Thanks to the simultaneous observations by ground magnetometers and the Arase satellite, the excitation mechanism of Pg was fully examined in this study. The azimuthal wave structure was estimated from the ground magnetometer stations to confirm whether the observed waves satisfy the resonance condition with energetic (110 keV) protons. Medium‐Energy Particle Experiments‐Ion Mass Analyzer onboard Arase is equipped with as many as 16 detectors of energetic ions and provides three‐dimensional flux data with the sufficient number of particle counts. We found a steep earthward gradient of proton phase space density from the data provided by Medium‐Energy Particle Experiments‐Ion Mass Analyzer and concluded that Pg observed in this event was excited through the wave‐particle interaction driven by the earthward gradient of the phase space density for protons at 110 keV. Key Points: Pc4 ULF waves and proton flux oscillations were observed by the Arase satellite and ground magnetometers The azimuthal wave number estimated from ground magnetometers is consistent with the theory of drift resonance The steep gradient of proton phase space density is responsible for the wave excitation